Agriculture and food security in the ECCU - Labadie, Beverley ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2008)
Assesses the challenges of food security faced by governments of the Eastern Caribbean Currency Union. Analyzes the policy measures implemented along with options available in ensuring that the nutritional needs of their populace are met.